PENILAIAN KUALITAS FISIKA DAN KIMIA GELATIN EKSTRAK DARI KAKI AYAM TUA (KAT) - Zulfikar Zulfikar; A.S. BABJI; W.M. WAN AIDA (State Islamic University of Sultan Syarif Kasim Riau, 2014)
This study aims to examine the physico chemical properties of gelatin extracted from spent hen with HCl pretreatment with immersion for 5 and 10 days. With extraction stages E1 temperature (45°C), E2 (65°C), and E3 75°C. Analysis results show there is significant difference (p<0.05) on the strength of bloom, the attribute color (b*has a negative value), and solubility. Respective is in the range ash content 1,10-2,26%, protein (68.91-79.86%), fat (1:10 to 2:26%), moisture (5.0-10.3%) and carbohydrate (10.1-20.84% ) for SCF 5, while the SCF 10. Ash (1.99-2.27%), protein (77.81-80.80%), fat (1:00 to 2:00%), moisture (5.0-7.0%), carbohydrate (9.58-12.60%).